INFLUENCE OF SQUID LIVER MEAL IN MATURATION DIET ON GONADOSOMATIC INDEX AND GONADAL AMINO ACID CONTENT OF GOLDEN SPOTTED RABBITFISH, Siganus guttatus - Asda Laining; Ike Trismawanti; Usman Usman; Muhammad Hafid Masruri (Indonesian Aquaculture Journal, 2019)
A four months feeding trial was conducted to evaluate the effects of two maturation diets containing either fishmeal (FM) or squid liver meal (SLM) as the major protein source on growth, gonadosomatic index and gonadal bio-chemical profiles of golden spotted rabbitfish, Siganus guttatus. The two tested diets were formulated to be iso-nitrogenous (40%) and iso-lipidic (14%) and supplemented with several micronutrients specifically for gonadal development. The initial weight of golden spotted rabbitfish used were 352.6 ± 45.0 g and stocked into four of 2 m x 2 m x 2.5 m net cages with 25 fish per cage. The test diets were fed to the stocks twice a day. After four months feeding, the weight gains (WG) of broodstock fed the two diets were nearly similar in which FM had WG of 40.1 ± 2.2% and 42.8 ± 2.0% for SLM. The GSI of male fed SLM diet was similar to that of fed with FM. However, the GSI of female fed FM was 5.6 ± 0.1% significantly lower (P<0.05) than SLM which was 11.4 ± 0.5%. Furthermore, total amino acid (TAA) in spermatocyte was significantly (P<0.05) influenced by dietary SLM indicated by its higher TAA (62.4%) compared to TAA content of FM group (46.1%). Similarly, the TAA content in oocyte was significantly (P<0.05) improved when fed SLM. The dietary SLM did not affect the TAA content in the fillet of rabbitfish demonstrated by the similarity of the fillet TAA content in the two groups which was 55.6% for FM and 54.1% for SLM. Dietary SLM enhanced GSI of female broodstocks and profile of amino acid in the gonad of golden spotted rabbitfish, Siganus guttatus.